OP0025 CD209+/CD14+ DENDRITIC CELLS ARE ENRICHED AND ACTIVATED AT THE SITE OF INFLAMMATION AND ARE MODULATED BY JAK/STAT SIGNALLING - Marzaioli, V.; Floudas, A.; Canavan, M.; Wade, S.; Murray, K.; Mullan, R.; Veale, D.; Fearon, U. (Annals of the rheumatic diseases, 2021)
Dendritic cells (DCs) are a heterogeneous population of professional antigen-presenting cells which are at the interface between innate and adaptive immunity. A specific subset of DCs is known to derive from monocyte and has a key role in inflammation and infection. This study aimed to characterize the phenotype and function of a distinct CD209+/CD14+ DC subset in the periphery and at the site of inflammation in patients with rheumatoid (RA) and psoriatic arthritic (PsA), in addition to examining the effect Tofacitinib and TNF inhibitor on their development. Peripheral blood and synovial fluid mononuclear cells (PBMC and SFMC) were isolated by Ficoll density gradient from healthy subject (HC), and patients with RA and PsA. Single cell synovial tissue suspension (ST) from RA and PsA patients were also established using enzymatic/mechanical digestion. PBMC, SFMC and ST were analysed by flow cytometry to identify the CD209+/CD14+ DC subset, its frequency and the cell surface expression of chemokines receptors (CCR6, CCR7, CXCR3, CXCR4 and CXCR5) and activation markers (CD40 and CD80). In addition, PBMC were stimulated with different TLR (LPS, CPG, R848, Poly I:C) and intracellular staining for IL12, TNFα, IL1β and IL6 was performed by flow cytometry. Lineage negative cells (CD3/CD19/CD56-) were stimulate with GMCSF/IL4 in the presence or absence of the JAK/STAT inhibitor Tofacitinib or the TNF inhibitor Humira, and the CD209+/CD14+ DC development was evaluated by flow cytometry. We identified, for the first time, a distinct CD209+/CD14+ DC population in PBMC of patients with RA and PsA, with similar frequency across the groups. However, when PBMC were stimulated with TLRs, an increase of IL12 and TNFα was observed in RA and PsA PBMC when compared to HC. Interestingly, this distinct DC population was significantly enriched at the site of inflammation, in both SFMC and ST, displaying a more mature phenotype, evident by the observed significant increase in CD40 and CD80 expression. SPICE analysis further identified differential expression and co-expression of chemokine receptors at the periphery of RA and PsA patients, when compared to the HC. Furthermore synovial tissue single cell analysis from RA/PsA demonstrated a unique chemokines receptors profile demonstrating increased single expression and co-expression of CXCR3 and CXCR5 compared to periphery. Finally, we have previously observed that JAK/STAT is involved in monocyte-derived dendritic cells population development (1,2), therefore we performed CD3, CD19 and CD56 depletion of RA/PsA PBMC followed by stimulation with GMCSF/IL4, to spike the Mo-DC population, in the presence of Tofacitinib or Humira. Interestingly, we observed that JAK/STAT inhibition, but not TNF inhibitor, reduced the generation and development of CD209+/CD14+ DC. We identify for the first time a distinct monocyte-derived DC population characterized as CD209+/CD14+ in the periphery of RA and PsA patients. This population was enriched at the site of inflammation and displayed a unique chemokine receptor profile and activation markers, suggesting that these cells are already activated in the periphery of IA patients, and are recruited and further activated in the inflamed joint. In addition, we showed that the CD209+/CD14+ DC development is regulated by JAK/STAT signalling, but not TNF inhibition. [1]Marzaioli V, Canavan M, Floudas A, et al. Monocyte-Derived Dendritic Cell Differentiation in Inflammatory Arthritis Is Regulated by the JAK/STAT Axis via NADPH Oxidase Regulation. Front. Immunol. 2020;11:1406. [2]Marzaioli V, Hurtado-Nedelec M, Pintard C, et al. NOX5 and p22phox are 2 novel regulators of human monocytic differentiation into dendritic cells. Blood. 2017;130(15):1734–1745. The authors also wish to thank all the patients who volunteered to participate into this study and the funding Viviana Marzaioli: None declared, Achilleas Floudas: None declared, Mary Canavan: None declared, Siobhan Wade: None declared, Kieran Murray: None declared, Ronan Mullan: None declared, Douglas Veale Speakers bureau: Abbvie, Janssen, Novartis, MSD, Pfizer, UCB, Consultant of: Abbvie, Janssen, Novartis, MSD, Pfizer, UCB, Grant/research support from: Janssen, Abbvie, Pfizer, UCB, Ursula Fearon Speakers bureau: Abbvie, Grant/research support from: Janssen, Abbvie, Pfizer, UCB